AtATM3 Is Involved in Heavy Metal Resistance in Arabidopsis - Kim, Do-Young (American Society of Plant Biologists, 2006)
AtATM3, an ATP-binding cassette transporter of Arabidopsis (Arabidopsis thaliana), is a mitochondrial protein involved in the biogenesis of iron-sulfur clusters and iron homeostasis in plants. Our gene expression analysis showed that AtATM3 is up-regulated in roots of plants treated with cadmium [Cd(II)] or lead (II); hence, we investigated whether this gene is involved in heavy metal tolerance. We found that AtATM3-overexpressing plants were enhanced in resistance to Cd, whereas atatm3 mutant plants were more sensitive to Cd than their wild-type controls. Moreover, atatm3 mutant plants expressing 35S promoter-driven AtATM3 were more resistant to Cd than wild-type plants. Since previous reports often showed that the cytosolic glutathione level is positively correlated with heavy metal resistance, we measured nonprotein thiols (NPSH) in these mutant plants. Surprisingly, we found that atatm3 contained more NPSH than the wild type under normal conditions. AtATM3-overexpressing plants did not differ under normal conditions, but contained less NPSH than wild-type plants when exposed to Cd(II). These results suggest a role for AtATM3 in regulating cellular NPSH level, a hypothesis that was further supported by our gene expression study. Genetic or pharmacological inhibition of glutathione biosynthesis led to the elevated expression of AtATM3, whereas expression of the glutathione synthase gene GSH1 was increased under Cd(II) stress and in the atatm3 mutant. Because the closest homolog of AtATM3 in fission yeast (Schizosaccharomyces pombe), HMT1, is a vacuolar membrane-localized phytochelatin-Cd transporter, it is tempting to speculate that glutathione-Cd(II) complexes formed in the mitochondria are exported by AtATM3. In conclusion, our data show that AtATM3 contributes to Cd resistance and suggest that it may mediate transport of glutamine synthetase-conjugated Cd(II) across the mitochondrial membrane.